RANCANGAN PELATIHAN YANG IDEAL DI DOULOS PHOS THE SHIP HOTEL - Tasya Wal Zahra; Muhammad Ikhsan Daniel; Seti Cindy Cahyani (JURNAL MATA PARIWISATA, 2025)
In designing ideal training, of course, the company does everything best to create a quality workforce, researchers have made observations before getting more results regarding research data information, after making observations, researchers find problems that occur, such as the lack of implementation of training for employees, in addition there are several formulations of problems that want to be studied more deeply, such as effectiveness in training, good time implementation and how management designs the training training. In order to achieve this desire, Training Need Analysis (TNA) is needed. By implementing this, the management can find out what needs are needed to realize a quality workforce. In this study, the method used to obtain research result was a qualitative method. Furthermore, the researcher conducted interviews with Mr. Andri Harris as Human Resources Manager and also with several employees at Doulos Phos The Ship Hotel. The management tries to be more consistent in carrying out training in a monthly month and see if there is any progress with the training provided 1 year.